2022
DOI: 10.1371/journal.pone.0270901
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes self-management and its associated factors among patients with diabetes in central Vietnam: A cross-sectional study

Abstract: Objective Diabetes self-management (DSM) enables maintenance of optimal individualized glycemic control for patients with diabetes through comprehensive lifestyle, medication adherence, and self-monitoring glucose level. This study aimed to evaluate DSM and to find associated factors among Vietnamese diabetes patients by using the Vietnamese version of Diabetes Self-Management Instrument (DSMI). Methods A cross-sectional study was conducted at a single hospital in the central Vietnam. DSM was assessed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
7
1
Order By: Relevance
“…HbA1c levels than others, which may be because they have more free time and energy to self-manage diabetes and communicate with doctors. 33 The level of health beliefs of the study participants was low, which was lower than the findings of Noppamas et al 34 This may be due to the older age, long course of disease, lack of knowledge about the disease, and presence of other chronic comorbidities of the participants that affected their health beliefs to varying degrees. The study showed that health beliefs were significantly negatively associated with HbA1c levels and could be used as a negative predictor of HbA1c control, health beliefs may contribute to poor glycaemic control in patients through differences in perceived susceptibility, perceived severity, perceived benefits, perceived barriers, and cues to action.…”
Section: Dovepresscontrasting
confidence: 60%
See 1 more Smart Citation
“…HbA1c levels than others, which may be because they have more free time and energy to self-manage diabetes and communicate with doctors. 33 The level of health beliefs of the study participants was low, which was lower than the findings of Noppamas et al 34 This may be due to the older age, long course of disease, lack of knowledge about the disease, and presence of other chronic comorbidities of the participants that affected their health beliefs to varying degrees. The study showed that health beliefs were significantly negatively associated with HbA1c levels and could be used as a negative predictor of HbA1c control, health beliefs may contribute to poor glycaemic control in patients through differences in perceived susceptibility, perceived severity, perceived benefits, perceived barriers, and cues to action.…”
Section: Dovepresscontrasting
confidence: 60%
“… 32 In addition, retirees have lower HbA1c levels than others, which may be because they have more free time and energy to self-manage diabetes and communicate with doctors. 33 …”
Section: Discussionmentioning
confidence: 99%
“…However, adolescents’ and young adults’ (AYAs’) self-management levels notably lag behind other age groups [ 20 ], resulting in severe consequences like hypoglycemia and diabetic ketoacidosis (DKA), a critical and acute complication in which the body produces an overabundance of blood acids (ketones) and often results in hospitalization [ 23 ]. Hence, swiftly and effectively performing, adapting, and adjusting daily self-care practices [ 34 , 54 ], referred to as T1D self-management routines , are imperative for optimal glycemic control (i.e., maintaining blood glucose levels within the targeted range).…”
Section: Introductionmentioning
confidence: 99%
“…Healthy selfmanagement behaviors in DM patients include Copyright © Author, 2023. Nursing Journal of Respati Yogyakarta, p-ISSN: 2088-8872; e-ISSN: 2541-2728 following a healthy diet, increasing physical activity, using DM drugs and drugs in special circumstances safely and regularly, and monitoring Blood glucose levels (Nguyen et al, 2022). Diabetes Mellitus sufferers are at high risk of experiencing complications in the form of hypoglycemia, hyperglycemia, ketoacidosis, and neuropathy which increases the risk of gangrenous wounds that lead to amputation, retinopathy which has the potential to cause blindness, nephropathy, which can lead to kidney failure (Balaji et al, 2019).…”
Section: Introductionmentioning
confidence: 99%